Gut microbiota short-chain fatty acids and their impact on the host thyroid function and diseases - Mendoza-León, María José; Mangalam, Ashutosh K.; Regaldiz, Alejandro; González-Madrid, Enrique; Rangel-Ramírez, Ma. Andreina; Álvarez-Mardonez, Oscar; Vallejos, Omar P.; Méndez, Constanza; Bueno, Susan M.; Melo-González, Felipe; Duarte, Yorley; Opazo, Ma. Cecilia; et al. (Frontiers in Endocrinology, 2023)
Thyroid disorders are clinically characterized by alterations of L-3,5,3',5'-tetraiodothyronine (T4), L-3,5,3'-triiodothyronine (T3), and/or thyroid-stimulating hormone (TSH) levels in the blood. The most frequent thyroid disorders are hypothyroidism, hyperthyroidism, and hypothyroxinemia. These conditions affect cell differentiation, function, and metabolism. It has been reported that 40% of the world's population suffers from some type of thyroid disorder and that several factors increase susceptibility to these diseases. Among them are iodine intake, environmental contamination, smoking, certain drugs, and genetic factors. Recently, the intestinal microbiota, composed of more than trillions of microbes, has emerged as a critical player in human health, and dysbiosis has been linked to thyroid diseases. The intestinal microbiota can affect host physiology by producing metabolites derived from dietary fiber, such as short-chain fatty acids (SCFAs). SCFAs have local actions in the intestine and can affect the central nervous system and immune system. Modulation of SCFAs-producing bacteria has also been connected to metabolic diseases, such as obesity and diabetes. In this review, we discuss how alterations in the production of SCFAs due to dysbiosis in patients could be related to thyroid disorders. The studies reviewed here may be of significant interest to endocrinology researchers and medical practitioners.